2019
DOI: 10.4314/njb.v35i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of OvineSNP50 in Nigerian and Kenyan sheep populations

Abstract: Deciphering genomic information requires markers that are polymorphic and sufficient enough to capture its vast array of genetic data. Polymorphic loci can differ greatly between breeds of the same species and the exclusion of the Nigerian and some African sheep breeds during the development of the OvineSNP50 chip necessitated the validation of SNPs included on the chip to allow for genomic applications of the excluded breeds. A total of sixty sheep samples were genotyped [10 each of the Balami, Uda, West Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Many molecular markers such as RAPD (Kunene et al, 2009), AFLP (De Marchi et al, 2006), PCR-RFLP (Kucharski et al, 2019), and mtDNA (Kirikci et al, 2018) have been applied to detect genetic diversity in livestock. Today, SSRs (simple sequence repeats (Demir and Balcioglu, 2019) and SNPs (single nucleotide polymorphisms) (Ilori et al, 2018) and NGS (next-generation sequencing) (Kijas et al, 2009) are preferred to reveal genetic diversity among and within different livestock breeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many molecular markers such as RAPD (Kunene et al, 2009), AFLP (De Marchi et al, 2006), PCR-RFLP (Kucharski et al, 2019), and mtDNA (Kirikci et al, 2018) have been applied to detect genetic diversity in livestock. Today, SSRs (simple sequence repeats (Demir and Balcioglu, 2019) and SNPs (single nucleotide polymorphisms) (Ilori et al, 2018) and NGS (next-generation sequencing) (Kijas et al, 2009) are preferred to reveal genetic diversity among and within different livestock breeds.…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers were used to detect genetic diversity or parentage test in different livestock including cattle (Demir and Balcioglu, 2019), sheep (Ocampo et al, 2016), goat (Jawasreh et al, 2018, pigs (Szmatoła et al, 2016), horses (Semik and Zabek, 2013) chickens (Karsli and Balcioglu, 2019), rabbit (Abdel-Kayf et. al., 2016), ducks (Hariyono et al, 2019, and donkeys (Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The OvineSNP50 BeadChip has been used in many applications which included genome-wide selection, comparative genetic studies, and breed characterization for evaluating biodiversity [35, 36, 37]. It was validated by Illumina for genotyping of more than 3000 samples from diverse Ovis aries domestic and wild breeds [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ovine genetic polymorphisms affect the physicochemical properties of milk hence, there is need for in-depth knowledge of the genetic polymorphism of indigenous ovine milk proteins for the improvement of the quality of ovine milk for its contribution to the Nigerian dairy industry. The genetic basis for diversity in sheep and its consequences on selection on gene polymorphism within the sheep breeds have not been assayed on a genomic scale worldwide [8]. Similarly, to our knowledge, there are no studies on variation in the alpha-casein gene of yankasa breed of sheep.…”
Section: Introductionmentioning
confidence: 99%